Endovascular therapy versus medical management in isolated posterior cerebral artery acute ischemic stroke: a multinational multicenter propensity score-weighted study - Salim, Hamza; Pulli, Benjamin; Yedavalli, Vivek; Musmar, Basel; Adeeb, Nimer; Lakhani, Dhairya; Essibayi, Muhammed Amir; El Naamani, Kareem; Henninger, Nils; Sundararajan, Sri Hari; Kühn, Anna Luisa; Khalife, Jane; et al. (European stroke journal, 2025)
BACKGROUND: Despite the proven effectiveness of endovascular therapy (EVT) in acute ischemic strokes (AIS) involving anterior circulation large vessel occlusions, isolated posterior cerebral artery (PCA) occlusions (iPCAo) remain underexplored in clinical trials. This study investigates the comparative effectiveness and safety of EVT against medical management (MM) in patients with iPCAo. - METHODS: This multinational, multicenter propensity score-weighted study analyzed data from the Multicenter Analysis of primary Distal medium vessel occlusions: effect of Mechanical Thrombectomy (MAD-MT) registry, involving 37 centers across North America, Asia, and Europe. We included iPCAo patients treated with either EVT or MM. The primary outcome was the modified Rankin Scale (mRS) at 90 days, with secondary outcomes including functional independence, mortality, and safety profiles such as hemorrhagic complications. - RESULTS: A total of 177 patients were analyzed (88 MM and 89 EVT). EVT showed a statistically significant improvement in 90-day mRS scores (OR = 0.55, 95% CI = 0.30-1.00, p = 0.048), functional independence (OR = 2.52, 95% CI = 1.02-6.20, p = 0.045), and a reduction in 90-day mortality (OR = 0.12, 95% CI = 0.03-0.54, p = 0.006) compared to MM. Hemorrhagic complications were not significantly different between the groups. - CONCLUSION: EVT for iPCAo is associated with better neurological outcomes and lower mortality compared to MM, without an increased risk of hemorrhagic complications. Nevertheless, these results should be interpreted with caution due to the study's observational design. The findings are hypothesis-generating and highlight the need for future randomized controlled trials to confirm these observations and establish definitive treatment guidelines for this patient population.